The Dehumanizing Violence Index: an Old World/new World Comparison of Overkill in Archaeological Contexts - (:unkn) unknown (My University, 2023)
THE DEHUMANIZING VIOLENCE INDEX: AN OLD WORLD/NEW WORLD COMPARISON OF OVERKILL IN ARCHAEOLOGICAL CONTEXTS Paul J. Moriarity The University of Wisconsin-Milwaukee, 2023Under the Supervision of Professor Bettina Arnold Extreme forms of violent behavior appear in various cultural contexts throughout human history. This study compares so-called “overkill” sites from the late Central European Neolithic and the Pueblo Period of the American Southwest to develop a systematic approach to distinguishing between the levels of violence exhibited in overkill assemblages, compare and define possible motivations and choices for extreme violent behavior, and determine whether the purposeful use of extreme violence in temporally and spatially distant cultures has predictive value today. The skeletal data from six overkill sites, three from each geographic context, were compared by means of an ordinal index, the Dehumanizing Violence Index (DVI), that incorporates variables across age and sex categories, including injury and trauma types and locations, evidence for perimortem torture and mutilation, and systematic extreme processing of the body. Although some overkill sites in the geographically and temporally distant contexts compared here appear similar in the treatment of victims, there are clear distinctions in local expression. Resource unpredictability during times of climatic instability was revealed as a strong predictive indicator for the manifestation of extreme violence, with outsider groups often serving as the main targets of such treatment.Key words: LBK, Pueblo cultures, overkill, Dehumanizing Violence Index, poetics of violence